Mineralocorticoid receptor antagonists for chronic heart failure: a meta-analysis focusing on the number needed to treat - Geng, Chang; Mao, Yu-Cheng; Qi, Su-fen; Song, Kai; Wang, Hong-Fei; Zhang, Zi-yan; Tian, Qing-Bao (Frontiers in Cardiovascular Medicine, 2023)
Aims Recent studies have shown that mineralocorticoid receptor antagonists (MRAs) can decrease mortality in patients with heart failure; however, the application of MRAs in current clinical practice is limited because of adverse effects such as hyperkalemia that occur with treatment. Therefore, this meta-analysis used the number needed to treat (NNT) to assess the efficacy and safety of MRAs in patients with chronic heart failure. Methods We meta-analysed randomized controlled trials (RCTs) which contrasted the impacts of MRAs with placebo. As of March 2023, all articles are published in English. The primary outcome was major adverse cardiovascular events (MACE), and secondary outcomes included all-cause mortality, cardiovascular death, myocardial infarction (MI), stroke, and adverse events. Results We incorporated seven studies with a total of 9,056 patients, 4,512 of whom received MRAs and 4,544 of whom received a placebo, with a mean follow-up period of 2.1 years. MACE, all-cause mortality, and cardiovascular mortality were all reduced by MRAs, with corresponding numbers needed to treat for benefit (NNTB) of 37, 28, and 34; as well as no impact on MI or stroke. MRAs increased the incidence of hyperkalemia and gynecomastia, with the corresponding mean number needed to treat for harm (NNTH) of 18 and 52. Conclusions This study showed that enabling one patient with HF to avoid MACE required treating 37 patients with MRAs for 2.1 years. MRAs reduce MACE, all-cause mortality, and cardiovascular death; however, they increase the risk of hyperkalemia and gynecomastia.